Efficacy of Dapoxetine in the Treatment of Premature Ejaculation - McMahon, Chris G. (Libertas Academica, 2011)
INTRODUCTION: Premature ejaculation (PE) is a common male sexual disorder which is associated with substantial personal and interpersonal negative psychological factors. Pharmacotherapy of PE with off-label antidepressant SSRI drugs is common. Development and regulatory approval of drugs specifically for the treatment of PE will reduce reliance on off-label treatments and serve to fill a unmet treatment need. AIM: To review evidence supporting the efficacy and safety of dapoxetine in the treatment of PE. METHODS: MEDLINE and the proceedings of major international and regional scientific meetings during the period 1994–2010 were searched for publications or abstracts using the word dapoxetine in the title, abstract or keywords. This search was then manually cross-referenced for all papers. This review encompasses studies of dapoxetine pharmacokinetics, animal studies, human phase 1, 2 and 3 efficacy and safety studies and drug-interaction studies. RESULTS: Dapoxetine is a potent selective serotonin re-uptake inhibitor, which is administered on-demand 1–3 hours prior to planned sexual contact. Dapoxetine is rapidly absorbed and eliminated, resulting in minimal accumulation and has dose-proportional pharmacokinetics, which are unaffected by multiple dosing. Dapoxetine 30 mg and 60 mg has been evaluated in 5 randomized, double-blind, placebo-controlled studies in 6081 men aged ≥18 years. Outcome measures included stopwatch-measured intravaginal ejaculatory latency time (IELT), Premature Ejaculation Profile (PEP) inventory items, clinical global impression of change (CGIC) in PE, and adverse events. Mean IELT, all PEP items and CGIC improved significantly with both doses of dapoxetine vs. placebo (P < 0.001 for all). The most common treatment related adverse effects included nausea (11.0% for 30 mg, 22.2% for 60 mg), dizziness (586% for 30 mg, 10.9% for 60 mg), and headache (5.6% for 30 mg, 8.8% for 60 mg), and evaluation of validated rated scales demonstrated no SSRI class-related effects with dapoxetine use. CONCLUSION: Dapoxetine, as the first drug developed for PE, is an effective and safe treatment for PE and represents a major advance in sexual medicine.